Development of an E-Module Assisted by Augmented Reality on Digestive System Material to Improve Elementary Students' Critical Thinking Skills - Adinda Zulfa Kamila; Aldina Eka Andriani (Jurnal Pijar MIPA, 2026)
Digital teaching materials, such as e-modules in basic science that utilise technology, have not yet been implemented in learning, resulting in 56% of students having low critical thinking skills. This study aims to describe the development design and to test the feasibility and effectiveness of an Augmented Reality-assisted e-module to improve the critical thinking skills of V-grade students at SDN Pendrikan Lor 03, Semarang City. This type of research is Research & Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects were 25 V-grade students. The data collection technique used non-test methods (observation, interviews, questionnaires, and documentation) and test methods (pretest and posttest). The data analysis technique used normality tests, homogeneity tests, t-tests, and N-Gain tests. The feasibility of the e-module assisted by Augmented Reality is proven by the assessment of the material expert validator of 91% and the media expert validator of 95% in the very feasible category, supported by the results of the teacher response questionnaire analysis of 92.5% and the student response questionnaire of 90.3% in the very feasible category. The effectiveness of the e-module assisted by Augmented Reality is evidenced by an increase in pretest and posttest scores of 20.26, supported by a t-test result of 0.000, and an N-Gain score of 0.5314, which falls within the medium range. The research on the e-module assisted by Augmented Reality for the digestive system material was successfully developed, is very feasible, and is effective in improving the critical thinking skills of V-grade students at SDN Pendrikan Lor 03, Semarang City.